2003
DOI: 10.1007/s00066-003-0976-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gross Tumor Volume (GTV) and Clinical Target Volume (CTV) Definition on the Total Accuracy in Radiotherapy

Abstract: Consequences to reduce interobserver variability are proposed, among others the selection of adequate imaging modalities, intensified radiologic training, and the use of telecommunication tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
132
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(137 citation statements)
references
References 36 publications
4
132
0
1
Order By: Relevance
“…Intra-observer variation is either in agreement or smaller than inter-observer variation similarly to previously reported clinical findings [5]. Disagreement between the same TPS is evident for contours generated using auto-threshold tools in the same TPS by different observers, (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Intra-observer variation is either in agreement or smaller than inter-observer variation similarly to previously reported clinical findings [5]. Disagreement between the same TPS is evident for contours generated using auto-threshold tools in the same TPS by different observers, (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Knowledge of these baseline values is important for clinical trials which commonly occur across multiple centres and TPSs. Current literature does not give clear guidelines for reporting contouring variability in inter-observer studies [4] with variation in methodology and metrics only enabling comparison between inter-observer studies in a limited fashion [5]. As such, calculating multiple metrics including a combination of descriptive statistics, overlap measures and statistical measures of agreement is recommended for multiple observer studies [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, CTV delineation uncertainties exist and should be included in the CTV for a more accurate margin to a better tumor control. Weiss and Hess (17) suggested that interobserver variability in target delineation was a major factor causing treatment inaccuracy. The delineation uncertainty can be reduced by using multimodality imaging as suggested by Rasch et al (18) The overall CTV‐to‐PTV margin, including tumor delineation, setup uncertainties, and internal organ displacement, should be fully investigated before determining PTV margin.…”
Section: Discussionmentioning
confidence: 99%
“…Delineating treatment targets within DICOM files is complex, operator-dependent, and critical to the accurate delivery of conformal radiotherapy [11][12][13][14][15]. These variabilities in target volume delineation can be a major primary source of inaccuracy of dose delivery and treatment errors [16]. Consequently, efforts have been made to identify processes in the target delineation process amenable to improvement, such as multimodality image incorporation [8,[17][18][19][20][21][22], instructional modification [23][24][25], visual atlas usage [11-15, 26, 27], window-level adjustment [28], autosegmentation [29,30], and software-assisted contouring [25].…”
Section: Discussionmentioning
confidence: 99%